IMPORTANT NORMS AND SUBJECTIVE NORMS ON GAY ADOLESCENT SEXUAL BEHAVIOR IN SEMARANG CITY - Larasaty, Nurina Dyah; Tursinawati, Yanuarita (Universitas Muhammadiyah Semarang, 2017)
Adolescents with a gay sexual orientation need to receive a great attention in cases of HIV / AIDS transmission.It is due to the sexual behavior in this class included in the category of risk behavior, one of which is through the anal sex. Anal intercourse is very risky in HIV transmission because the penis can scratch and tear the rectal mucous membranes, so that HIV can more smoothly enter the bloodstream.The purpose of this study is to explore the information about important and subjective norms of gay adolescents in Semarang City. This research used qualitative approach. Data collection was done through in-depth interviews with informants as well as field observations. The results of this study found that the important norm prevailing in the family associated with acceptance of sexual orientation of familymembers as gay according to most informants stated the rejection. However, a small percentage of informants thought the rejection of the family would turn into acceptance over time. In contrast to the subjective norms prevailing in the community, all informants argue that the community still strongly rejects the existence of this gay group. This is contrary to the norms of religion and social normsprevailing in Indonesian society. Keywords: Important Norm, Subjective Norm, Sexual Behavior, Gay